Dark and bright mode hybridization: From electric to magnetic Fano resonances. (January 2016) - Panaro, S.; De Angelis, F.; Toma, A.
Abstract: The excitation of plasmonic Fano resonances leads to a dual advantage in nano-photonics, in terms of local field enhancement and far-field spectral selectivity. Nevertheless, a remarkable challenge related to the hybridization between bright and dark plasmonic modes, i.e. between the two elements cooperating to the Fano resonance generation, consists in the sub-wavelength activation of dark modes via near-field channel. In this regard, strongly coupled plasmonic nano-assemblies are ideal systems providing a highly efficient way towards their excitation. Here, we analyze two trimer nano-architectures supporting respectively electric and magnetic Fano resonances. The different approaches employed for describing the two systems highlighted the role that the near-field coupling and the LSPs de-phasing separately play in the Fano hybridization phenomena. Highlights: Plasmonic Fano resonant nanostructures for bio-detection. Theoretical analysis of near-field coupling and LSPs de-phasing in Fano resonances. Excitation of electric and magnetic hot-spots in Fano resonance condition.